2002
DOI: 10.1001/archderm.138.12.1593
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Using Escharotic Agents as Primary Treatment for Nonmelanoma Skin Cancer

Abstract: Background: The use of escharotic or caustic pastes to treat skin cancer is based on the centuries-old observation that selected minerals and plant extracts may be used to destroy certain skin lesions. Zinc chloride and Sanguinaria canadensis (bloodroot) are 2 agents that are used as part of the Mohs chemosurgery fixed-tissue technique. The use of escharotics without surgery has been discredited by allopathic medicine but persists and is promoted among alternative practitioners. Patients may now purchase "herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 6 publications
(5 reference statements)
1
55
0
2
Order By: Relevance
“…The other applications of zinc chloride include protein precipitation and insulin preparation [10,11]. Literature reported that zinc chloride has been used in the treatment of cancer as a destructive agent [12] and in the pluripotency maintenance of mouse embryonic stem cell through the regulation of STAT3 signaling pathway [13]. It can be used for the palliative treatment of canine and malignant skin wounds [14].…”
Section: Introductionmentioning
confidence: 99%
“…The other applications of zinc chloride include protein precipitation and insulin preparation [10,11]. Literature reported that zinc chloride has been used in the treatment of cancer as a destructive agent [12] and in the pluripotency maintenance of mouse embryonic stem cell through the regulation of STAT3 signaling pathway [13]. It can be used for the palliative treatment of canine and malignant skin wounds [14].…”
Section: Introductionmentioning
confidence: 99%
“…The criticism of such treatments in medical literature generally addresses cases where individual patients refused the medical standard of care treatment in favor of self-prescribed, unsupervised treatment with an escharotic concoction purchased by the patient through the Internet. 8,9 This report provides evidence for the efficacy of escharotic treatment for CIN II, III in a case of recurrent, highgrade neoplasia following conventional cervical conization. The strength of this case emphasizes the need for clinical research to explore the long-term effectiveness and potential risks of escharotic treatment for cervical dysplasia.…”
mentioning
confidence: 72%
“…Each ingredient already has been proven for its potential activity on skin health as evidenced through use in various medicines as well as cosmeceuticals. Zinc is an essential cofactor of various metalloenzymes and it protects the skin from UV irradiation and has been used as a destructive agent for the management of cancer [7,8]. Sodium selenate enhances the repair system of DNA segments and reduces the risk of new cancer development [9,10].…”
Section: Shirley Theresa Holmlundn Et Al: Skin Nourishing Effects Ofmentioning
confidence: 99%